Analysis ARFF Personel Knowledge In Efforts to Handle Emergencies In Waters - Sila Witama, I Made; Nugraha, Wildan (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Kualanamu International Airport is one of the aviation service providers with an airport layout within a radius of 5Mile (±8Km) from the airport reference point which includes water areas. Airports are required to ensure the safety of passengers in carrying out airport operations by ensuring that ARFF units have personnel with appropriate qualifications effectively and efficiently in providing services that cover waters. The purpose of this research is to find out how the level of knowledge of sea rescue ARFF personnel and the efforts made by the ARFF unit at Kualanamu International Airport in handling emergencies in the waters. It can be seen from the conditions in the field based on the results of observational data collection, literature studies, and interviews that the knowledge of ARFF personnel related to sea rescue is still relatively low. Furthermore, to analyze the data that has been collected, the author uses Gap Analysis by determining the gaps or gaps that occur in the field. The results of the research based on the data collected by the author show that there is a gap from the current condition to the desired condition according to the applicable regulations, namely the need for a routine training program related to sea rescue for ARFF personnel in an effort to handle emergencies in the waters. The conclusion of this study is that ARFF personnel at Kualaanamu International Airport need to design a training program